ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INITIAL RETURN PADA PENAWARAN PERDANA SAHAM DI BURSA EFEK INDONESIA SAAT KRISIS FINANSIAL GLOBAL PERIODE 2006-2008 - Abubakar Arif; Febrina Nur Isnidya (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2010)
This objective of the research is to analyze influence of Initial Return on global financial crisis period in the period 2006-2008, obtained from non-financial information and financial support for taken into consideration in decisions to invest in companies that do an IPO on the Indonesia Stock Exchange. Tests conducted on 45 companies that went public in the year 2006-2008 in the Indonesia stock exchange, the sample selection method sampling purposive. The main issues underlying this research is to determine the influence of company size, earnings per share, price earning ratio, the level of leverage, return on total assets, the percentage of old shareholders, auditor reputation and the reputation of underwriters, the initial period of return on the global financial crisis. The results showed that simultaneous testing of a significant effect between the independent variables both financial and non financial measures consist of the company, earnings per share, price earning ratio, the level of leverage, return on total assets, the percentage of old shareholders, auditor reputation, and underwriter's reputation with its dependent variable is initial return on the global financial crisis period of 2006-2008. While on a partial test of financial information variable earnings per share which is partially a significant effect on initial returns, and on non-financial information that affects a significant is auditor reputation ofthe initial return.